Avoiding a crisis at Christmas: a systematic review of adverse health effects or 'Chrishaps' caused by traditional hazard sources and COVID‐19. (23rd December 2021) - Wild, Ursula; Shaw, David M.; Erren, Thomas C.
Abstract: Objective : To complement the 2020 ANZJPH editorial "How COVID‐safe Santa can save Christmas". In addition to a concise update regarding SARS‐CoV‐2/COVID‐19, we aimed to explore some risks of Christmas in terms of adverse health effects, which we call 'Chrishaps'. Our overall study question was "which hazards have been scientifically associated with old Christmas essentials such as decoration, gifts, menus, and Santa himself, as well as new challenges associated with COVID‐19?" Method : We searched the PubMed, Web of Science, and Open Grey databases systematically and Google unsystematically. Results : Thirty‐six pertinent articles – most of them case reports or retrospective analyses – documented Chrishaps. Conclusion : Overall results suggested that Chrishaps come in different shapes and guises. Implications for public health : Chrishaps pose a potential minor public health threat that should be borne in mind every festive season. Assessing and discussing specific public health implications of Chrishaps requires systematic risk research to be conducted.